Hyping the Void: Zizek on Zizek - SEERY, AIDAN (My University, 2011)
This chapter examines the celebrity status, particularly in the public sphere but also in the academy, of the academic and intellectual Slavoj Zizek using a number of ideas from his own work to act as a mirror, as it were, on himself. It is structured in three parts. In the first part, I attempt a description of some aspects of the phenomenon of the celebrity intellectual and some of the factors that seem to be at play in the emergence, particularly in the 1990s, of this unlikely celebrity type. The second part uses the structure of Zizek?s critique of ideology as a way of illuminating what might be claimed to be three different types of celebrity. This is followed by some ideas from Zizek?s concept of the self that can be used to understand both the phenomenon of celebrity and possible ways of resisting the power of celebrity culture. In the final section, those aspects of Zizek?s thought considered earlier in the essay are turned on his own celebrity status in order to say something Zizekian about Zizek himself.
PUBLISHED
Keywords: Narrative; Biography studies; Identities in Transformation